Is Cytoreductive Nephrectomy Still Relevant in the Era of Targeted Therapy? A Retrospective Survival Study in Metastatic RCC from Nepal - Jalan, Aditya; Pokhrel, Gyan; Rana Gurung, Sarita; Gharti, Binod; Nepal, Umesh; Lamichhane, Nirmal (Nepalese Journal of Cancer, 2025)
Background: Metastatic renal cell carcinoma (mRCC) accounts for approximately 22% of all RCC cases and presents significant treatment challenges, especially in resource-limited settings like Nepal. Although the role of cytoreductive nephrectomy (CN) has been established in the immunotherapy era, its value in the era of targeted therapies remains controversial. This study evaluates overall survival (OS) outcomes among patients with synchronous mRCC treated with sunitinib, with or without prior CN, at a tertiary cancer center in Nepal. Methods: We conducted a retrospective study of 54 patients with synchronous mRCC who received first-line sunitinib therapy between January 2007 and December 2015 at B.P. Koirala Memorial Cancer Hospital. Patients were divided into two cohorts: those receiving CN followed by sunitinib (CN/TT) and those receiving sunitinib alone (TT). Baseline characteristics, MSKCC risk stratification, and survival outcomes were analyzed. OS was calculated from the start of therapy to death or last follow-up, using Kaplan-Meier analysis and log-rank test for group comparison. Results: Among the 54 patients included, 17 (31.5%) underwent CN followed by sunitinib, while 37 (68.5%) received sunitinib alone. The median OS for the entire cohort was 6 months (mean ± SD: 2.29 ± 2.35 months; 95% CI: 7.68–16.90). The 1-year, 3-year, and 5-year OS rates were 29%, 5%, and 2%, respectively. The CN/TT group demonstrated significantly improved survival compared to the TT group, with a median OS of 13 months versus 4 months. The 1-year, 3-year, and 5-year OS rates for the CN/TT group were 58%, 11%, and 6%, respectively, compared to 15%, 3%, and 2% in the TT group (p < 0.05). Most patients were classified as intermediate or poor risk according to MSKCC criteria Conclusion: This is the first study from Nepal demonstrating a survival benefit of cytoreductive nephrectomy in patients with synchronous mRCC treated with sunitinib. Despite limitations of retrospective design and sample size, our findings support the continued role of CN in select patients receiving targeted therapy, particularly in low-resource settings. Prospective studies are warranted to better define patient selection and optimize outcomes.